BRICS expansion in the news coverage of member countries: a political economy perspective - Fedaa Mohamed Abdelaziz Abdeldayem; Sarah Francis Wadie Kswat (Journal of Humanities and Applied Social Sciences)
Purpose – The purpose of this research is to examine the dynamics of news coverage within Brazil, Russia, India, China and South Africa (BRICS) nations, aiming to uncover patterns and critical factors influencing political and economic development policies. By providing a comprehensive overview of macro-level and sector-level economic trends reported by member country newspapers, the study seeks to understand problem-driven analysis schemes and proposed solutions to challenges. Additionally, it aims to evaluate the economic implications of political decisions as portrayed in news coverage, scrutinize the promotion of meaningful dialog and assess the role of news in encouraging coherence among stakeholders for effective pursuit of economic development goals within the BRICS nations. Design/methodology/approach – This qualitative research involves conducting a content analysis on 11 newspapers, each published by a BRICS member country, including established and recent members. The current study analyzes the national interests, economic implications of media frames, leaders’ statements and geopolitical contexts in light of the coverage of the newspapers under study and the BRICS' inclusion of new members from a political economy perspective. Findings – All eleven newspapers emphasize the significance of the BRICS Summit and its role in shaping economic and geopolitical dynamics. They consistently highlight the cooperative and multilateral nature of BRICS, focusing on collaboration among member nations. All newspapers emphasize the importance of the BRICS Summit as a key event in global geopolitics. For instance, they discuss the 2023 BRICS Summit in South Africa as a focal point for member countries to discuss various global issues. Each newspaper discusses BRICS' role in advocating for equitable global governance and challenging Western dominance in international affairs. Economic aspects, such as trade, financial cooperation and economic growth within BRICS, are mentioned in the coverage of all eleven newspapers, underlining the economic dimension of the group. All eleven newspapers explore the expansion of BRICS and its implications, including differing member opinions and the introduction of new member countries. However, The Buenos Aires Times (Argentina) provides an in-depth focus on Argentina’s admission to BRICS and its significance, reflecting its unique perspective as a potential member. All newspapers recognize the media’s role in shaping awareness and discourse related to BRICS, but The Buenos Aires Times specifically focuses on Argentina’s perspective and how it informs its readers about global developments. Also, unlike other newspapers, The Buenos Aires Times mentions domestic political factors, including presidential elections in Argentina and opposition to Argentina’s BRICS membership, which impact the country’s stance. The newspapers' coverage of BRICS reflects their national interests, priorities and perspectives. While geopolitical and economic aspects are prominent, the depth of analysis, the emphasis on specific economic trends and the extent of problem-driven analysis vary. These diverse viewpoints provide readers with a comprehensive understanding of BRICS and its global impact. When comparing the 11 newspapers' coverage of BRICS-related topics, it’s evident that each publication brings its unique perspective and priorities to the forefront. Research limitations/implications – While this research provides valuable insights into news patterns and their influence on political and economic development in BRICS nations, certain limitations should be acknowledged. The study’s scope primarily relies on newspaper coverage, potentially omitting perspectives from other media sources. Practical implications – The practical implications of this research are profound. Policymakers can leverage insights to craft informed strategies, and businesses and investors can gain a nuanced understanding of economic trends and media practitioners refine their coverage. The findings promote cross-cultural understanding within BRICS nations, encouraging cooperation. Global stakeholders can navigate the political-economic landscape more adeptly. Ultimately, the research provides actionable knowledge, facilitating effective decision-making, enhancing collaboration and contributing to the sustainable development and stability of the BRICS countries and the broader international community. Social implications – This research carries significant social implications by encouraging a deeper comprehension of the interplay between news media, politics and economics in BRICS nations. It promotes informed civic discourse, enabling citizens to critically engage with socio-political issues. By uncovering the media’s influence, the study contributes to media literacy, empowering the public to make informed decisions. Additionally, the research enhances cross-cultural understanding, potentially mitigating biases and stereotypes. Ultimately, it strengthens the social fabric by encouraging a more informed and engaged citizenry, capable of contributing positively to the political and economic development of their respective nations within the BRICS framework. Originality/value – This research contributes originality and value by offering a nuanced exploration of news patterns in BRICS nations, going beyond surface-level analysis. By focusing on macro- and sector-level economic trends, the study provides a unique perspective on the interplay between media narratives and economic development. The examination of problem-driven analysis and proposed solutions adds depth, offering insights into policy implications. Evaluating the economic implications of political decisions through news coverage enhances understanding. Furthermore, the research’s emphasis on promoting meaningful dialog and assessing the role of news in stakeholder coherence contributes distinctive insights, enhancing the broader understanding of the interconnections between media, politics and economic development in the BRICS context.